Enhanced bone size, microarchitecture, and strength in female runners with a history of playing multidirectional sports - Warden, S. J.; Sventeckis, A. M.; Surowiec, R. K.; Fuchs, R. K. (Medicine & Science in Sports & Exercise, 2022)
Purpose Female runners have high rates of bone stress injuries (BSIs), including stress reactions and fractures. The current study explored multidirectional sports (MDS) played when younger as a potential means of building stronger bones to reduce BSI risk in these athletes.